ANALISIS PRAKTEK TRADISI BESENTULAK DALAM PERSPEKTIF ISLAM DI DESA JEROWARU - Suparjon, Suparjon (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstrak: The Besentulak tradition is a rain-seeking practice still performed by some communities in Indonesia. This tradition typically involves customary rituals, prayers, and other forms of supplication to bring rain during prolonged droughts. This study aims to analyze the practice of the Besentulak tradition from an Islamic perspective using three main aspects: the aspect of faith (tauhid), the aspect of worship, and the aspect of Islamic law and morality.  The analysis results indicate that the Besentulak tradition can be categorized into two forms: first, those that align with Islamic teachings if they only involve supplications directed to Allah without elements of polytheism; second, those that contradict Islam if they include offerings, belief in supernatural forces besides Allah, or shamanistic practices. In Islam, rain supplication has been prescribed through Salat al-Istisqa’ and prayers taught by Prophet Muhammad (PBUH). Therefore, this tradition needs to be purified to uphold monotheistic values and comply with Islamic law.   Keyword: Besentulak ;Tradition; Islam. Abstrak: Tradisi Besentulak merupakan praktik meminta hujan yang masih dilakukan oleh sebagian masyarakat di Indonesia. Tradisi ini biasanya melibatkan ritual adat, doa, dan bentuk permohonan lainnya untuk mendatangkan hujan saat musim kemarau panjang. Penelitian ini bertujuan untuk menganalisis praktik tradisi Besentulak dalam perspektif Islam dengan menggunakan tiga aspek utama, yaitu aspek akidah (tauhid), aspek ibadah, dan aspek syariat serta akhlak Hasil analisis menunjukkan bahwa tradisi Besentulak dapat dikategorikan menjadi dua bentuk: pertama, yang masih sesuai dengan ajaran Islam jika hanya berupa doa kepada Allah tanpa unsur kesyirikan; kedua, yang bertentangan dengan Islam jika terdapat unsur sesaji, kepercayaan pada kekuatan selain Allah, atau praktik perdukunan. Dalam Islam, permohonan hujan telah diajarkan melalui salat istisqa’ dan doa-doa yang sesuai dengan tuntunan Rasulullah SAW. Oleh karena itu, diperlukan pemurnian praktik tradisi ini agar tetap menjaga nilai-nilai tauhid dan sesuai dengan syariat Islam.   Kata kunci: Besentulak; Tradisi; Islam.